Differential expressions of putative genes in various floral organs of the Pigeon orchid (Dendrobium crumenatum) using GeneFishing - Qamaruz Zaman, Faridah; Ng, Joey Boon Zean; Abdul Rahim, Raha; Abu Bakar, Umi Kalsom; Khosravi, Ali Reza (Academic Journals, 2009)
Nine Differentially Expressed Genes (DEGs) were detected in the five floral organs of Dendrobium crumenatum and three DEGs of relatively high expression in the column, were significantly homologous to the small Heat Shock Protein (HSP) differentially regulated during pollen development and heat stress in tobacco (DEG3-8), pectin methylesterase enzyme (PME) which was a male-flower specific gene in Salix gilgiana (DEG6-1) and the 14-3-3 protein which was differentially expressed and upregulated in Malus x domestica (DEG9-9) during fruit ripening. Generally, the differential expressions of the DEGs in the column and other floral organs were distinct, indicating the suppressive role of column DEGs on other floral organ DEGs. Interactions between the other floral DEGs (excluding column DEGs) indicated pattern expression specificity to each floral organ. Following this investigation, further molecular expression investigations are required and essential to develop and establish an orchid floral ontogenic model.